2013
DOI: 10.5171/2013.535319
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Associated Osteonecrosis of the Maxilla

Abstract: The authors make a review of the current literature on the subject of bisphosphonateassociated osteonecrosis of the jaw bones. The modern theories about the occurrence of this complication resulting from bisphosphonate treatment of diseases characterized with high bone resorption are discussed. Modern understandings about the causes, risk factors and triggers for the occurrence of this disease are described. Attention is paid to the modern concepts of medication therapy and surgical treatment. A case of bispho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Bamias A et al [5] suggests that there is a strong correlation between the duration of bisphosphonate treatment and manifestation of jaw osteonecrosis. They found that the risk of developing this condition varies from 1% (12 months after the start of treatment) to 11% in the fourth year.…”
Section: Triggering Factors Risk Factors Associated With Bisphosphonamentioning
confidence: 99%
“…Bamias A et al [5] suggests that there is a strong correlation between the duration of bisphosphonate treatment and manifestation of jaw osteonecrosis. They found that the risk of developing this condition varies from 1% (12 months after the start of treatment) to 11% in the fourth year.…”
Section: Triggering Factors Risk Factors Associated With Bisphosphonamentioning
confidence: 99%